Sex steroids and bone health in men - Ohlsson, Claes (Nature Publishing Group, 2012)
The influence of sex steroids on bone in both men and women has long been recognized. In men, however, the relative contribution of androgens versus estrogens in the regulation of bone metabolism remains uncertain. Animal studies demonstrate that both estradiol (E2), via activation of estrogen receptor-α, and testosterone (T), via activation of the androgen receptor, regulate bone mass in male rodents. The main focus of this review is to summarize and discuss recent findings from the osteoporotic fractures in men (MrOS) cohorts regarding the impact of serum sex steroids on bone health in elderly men. Collectively, these data demonstrate that serum E2 is directly associated with bone mineral density (BMD) and that low serum E2 associates with higher rates of bone loss and fracture. In addition, they substantiate the concept of a threshold E2 level that determines fracture risk in elderly men. We propose that the effect of E2 on fracture risk is at least partly mediated by its effect on BMD, whereas the more modest effect of T on fracture risk mainly is mediated by effects on muscle strength and risk of falls. Findings from the MrOS cohorts also demonstrate that racial and genetic variations in aromatase activity influence serum E2 levels in men. In conclusion, there is compelling evidence that not only androgens, but also estrogens, are important regulators of bone health in men. Consequently, E2 should not exclusively be regarded as the 'female hormone' but as a sex steroid that is necessary for maintenance of bone health in men.